2011
DOI: 10.1073/pnas.1015253108
|View full text |Cite
|
Sign up to set email alerts
|

Creation and manipulation of common functional groups en route to a skeletally diverse chemical library

Abstract: We have developed an efficient strategy to a skeletally diverse chemical library, which entailed a sequence of enyne cycloisomerization, [4 þ 2] cycloaddition, alkene dihydroxylation, and diol carbamylation. Using this approach, only 16 readily available building blocks were needed to produce a representative 191-member library, which displayed broad distribution of molecular shapes and excellent physicochemical properties. This library further enabled identification of a small molecule, which effectively supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…This necessitates the need for the design of diverse molecular libraries with high 3D‐content to crosstalk specifically with the high 3D‐content complementary in BACE1. This conclusion is supported by several examples of successful drug discoveries, which indicated that increasing the SP 3 ‐contents of a ligand to better suit the complementary binding regions of an active site correlates favorably with selectivity and the success rate in clinical trials . Moreover, recent reports illustrated that BACE1 inhibitors caused structural and functional synaptic impairment that accounts for safety concerns .…”
Section: Discussionmentioning
confidence: 80%
“…This necessitates the need for the design of diverse molecular libraries with high 3D‐content to crosstalk specifically with the high 3D‐content complementary in BACE1. This conclusion is supported by several examples of successful drug discoveries, which indicated that increasing the SP 3 ‐contents of a ligand to better suit the complementary binding regions of an active site correlates favorably with selectivity and the success rate in clinical trials . Moreover, recent reports illustrated that BACE1 inhibitors caused structural and functional synaptic impairment that accounts for safety concerns .…”
Section: Discussionmentioning
confidence: 80%
“…Several strategies have been followed to create these molecules, including pathway engineering 2 and diversity-oriented synthesis. 35 …”
Section: Introductionmentioning
confidence: 99%
“…One approach is diversity-oriented synthesis (DOS), where simple starting materials are coupled to make diverse structures that are more natural product-like in terms of size, percentage of sp 3 carbons, and number of stereogenic centers. 812 Other methods include the synthesis of natural product-inspired scaffolds that can be efficiently and differentially decorated, 1314 skeletal diversifications, 1517 use of natural product-derived building blocks for combinatorial synthesis, 18 biology-oriented synthesis, 19 and the synthesis of chiral and conformationally constrained oligomers. 20 …”
mentioning
confidence: 99%